Lectures on the Statutes of the Sacred Order of St. John of Jerusalem: at the University (of Studies) of Malta 1792 - Barz, Wolf-Dieter (2012)
The Statutes of the Order of Malta were compiled anew in 1776; they are still valid as subsidiary. Micallef, a Maltese Conventual Chaplain of the Order and professor at the Order's University of Malta, delivered lectures on the Statutes which were printed in a very limited number in 1791. Edited in English is included with the lectures' text. A brief history of the Order and of the University together with a short biography on Micallef; in appendix: the present Constitution and Code of the Order...